Digital Paradox in Indonesia's Govtech Transformation - Mubasyier Fatah; Yohanes Ngamal (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
The Indonesian government envisions Government Technology (GovTech) as a key accelerator toward Vision 2045 for modern and inclusive public services. However, despite massive investments in digital infrastructure from the Palapa Ring to INA Digital the implementation reveals a paradox between digital ambition and institutional reality. This study aims to critically examine the structural challenges hindering Indonesia’s GovTech transformation. Using a qualitative literature review, data were thematically analyzed from government reports, academic publications, and industry research. The findings highlight three core paradoxes: (1) persistent governance deficits and institutional weaknesses that undermine digital reforms; (2) a severe digital talent gap that limits system resilience; and (3) deepening socioeconomic inequality caused by uneven digital inclusion and cybersecurity vulnerabilities. The study concludes that Indonesia’s GovTech transformation remains a dialectic between utopian aspiration and systemic constraint. Its success depends on shifting from technological determinism toward strengthening governance, institutional accountability, and human capital. The study contributes original insight by framing the “utopian paradox” as a conceptual lens to explain how weak institutions systematically distort digital modernization efforts.